IMPLEMENTASI KEBIJAKAN INVESTASI PERIKANAN DAN KELAUTAN DI KOTA BITUNG - Chuang Jonathan; Fanley Pangemanan; Welly Waworundeng (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the implementation of the Fisheries and Marine Investment Policy in Bitung City. Investment policies generally aim to improve the overall investment climate, while investment promotion strategies have more measurable objectives that refer to the target amount of foreign investment a country or region wishes to attract within a specific timeframe. In an effort to increase the number of investors in Bitung City, the Bitung City government issued Regional Regulation No. 11 of 2019 concerning the Provision of Incentives and Facilitation of Investment to the Community and Investors in 2019. Investment growth in the fisheries sector in Bitung City still faces obstacles, with the number of investors remaining insignificant despite regulations facilitating investment in Bitung City, particularly investment from foreign capital or large companies, which are significantly outnumbered by small businesses operating in the fisheries sector. This study used qualitative research methods. The results indicate that the implementation of investment policies, particularly in the fisheries sector, is generally progressing well, but it requires resource support, particularly a sufficient budget, for its development.